Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г

Другие варианты решения
Раздел:

Номер №153

Упростите выражение:
а)
$(a^2 + 2a + 1) * (\frac{1}{a + 1} + \frac{1}{a^2 - 1} - \frac{1}{a - 1})$
;
б)
$(1 - \frac{9x^2 + 4}{12x}) : (\frac{1}{3x} - \frac{1}{2}) + 1$
;
в)
$1 - (\frac{2}{a - 2} - \frac{2}{a + 2}) * (a - \frac{3a + 2}{4})$
;
г)
$(y^2 - 4)(\frac{3}{y + 2} - \frac{2}{y - 2}) + 5$
.

Решение а

$(a^2 + 2a + 1) * (\frac{1}{a + 1} + \frac{1}{a^2 - 1} - \frac{1}{a - 1}) = \frac{(a + 1)^2}{1} * \frac{a - 1 + 1 - (a + 1)}{(a - 1)(a + 1)} = \frac{(a + 1) * (-1)}{a - 1} = \frac{1 + a}{1 - a}$

Решение б

$(1 - \frac{9x^2 + 4}{12x}) : (\frac{1}{3x} - \frac{1}{2}) + 1 = -\frac{9x^2 - 12x + 4}{12x} : (\frac{2 - 3x}{6x}) + 1 = -\frac{(3x - 2)^2}{12x} * \frac{6x}{2 - 3x} + 1 = \frac{(3x - 2)^2}{2} * \frac{1}{3x - 2} + 1 = \frac{3x - 2}{2} + 1 = \frac{3x - 2 + 2}{2} = 1,5x$

Решение в

$1 - (\frac{2}{a - 2} - \frac{2}{a + 2}) * (a - \frac{3a + 2}{4}) = 1 - (\frac{2(a + 2) - 2(a - 2)}{(a - 2)(a + 2)}) * \frac{4a - (3a + 2)}{4} = 1 - \frac{8}{(a - 2)(a + 2)} * \frac{(a - 2)}{4} = 1 - \frac{2}{a + 2} = \frac{a + 2 - 2}{a + 2} = \frac{a}{a + 2}$

Решение г

$(y^2 - 4)(\frac{3}{y + 2} - \frac{2}{y - 2}) + 5 = \frac{(y - 2)(y + 2)}{1} * \frac{3(y - 2) - 2(y + 2)}{(y - 2)(y + 2)} + 5 = 3y - 6 - 2y - 4 + 5 = y - 5$
Другие варианты решения